The addition of PD-1 inhibitor overcame trastuzumab resistance in patients with HER2 positive, PD-L1 negative metastatic gastric cancer: Case report and review of literature - Wen, Zhenpeng; Ye, Daoli; Hu, Qiancheng; Gou, Hongfeng (Frontiers in Pharmacology, 2024)
Gastric cancer (GC) is a malignancy with poor prognosis and high heterogeneity. For HER2-positive, PD-L1 negative metastatic GC patients, chemotherapy plus trastuzumab is the first-line therapy. However, such patients soon acquired resistance to treatment, especially to trastuzumab during the treatment. Improving the therapeutic resistance of HER2-positive, PD-L1 negative metastatic GC is still a dilemma. We present the case of a metastatic GC patient with HER2-positive and PD-L1-negative expression who suffered progression after a short remission with trastuzumab plus chemotherapy. The patient exhibited strong heterogeneity in the primary and metastatic lesions. His resistance to trastuzumab was overcome after the addition of a PD-1 inhibitor, after which he received a durable response for more than 8 months. In HER2-positive, PD-L1-negative metastatic GC, the addition of PD-1 inhibitors after first-line chemotherapy and trastuzumab treatment resistance may be an option.